2022
DOI: 10.4254/wjh.v14.i9.1817
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on use of palliative care for patients with alcohol related end stage liver disease in United States

Abstract: BACKGROUND Palliative care (PC) has been shown to be beneficial in end stage liver disease (ESLD), yet the hospitalization data for PC utilization is unknown. AIM To identify the trend of PC utilization for the special population of alcohol-associated ESLD patients, factors affecting its use and ascertain its impact on healthcare utilization. METHODS We analyzed around 78 million discharges from the 2007-2014 national inpatient sample and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our findings demonstrated that palliative care use increased during the study periods, which was consistent with earlier research on palliative care utilization in other chronic conditions. For example, a prior study discovered a 0.8-6.6% increase in all alcohol-associated end-stage liver disease hospitalized patients between 2007 and 2014 (22). Another retrospective study that implemented NIS determined that between 2005 and 2014, the proportion of patients with chronic obstructive pulmonary disease (COPD) receiving palliative care increased from 8.5% to 57.2% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that palliative care use increased during the study periods, which was consistent with earlier research on palliative care utilization in other chronic conditions. For example, a prior study discovered a 0.8-6.6% increase in all alcohol-associated end-stage liver disease hospitalized patients between 2007 and 2014 (22). Another retrospective study that implemented NIS determined that between 2005 and 2014, the proportion of patients with chronic obstructive pulmonary disease (COPD) receiving palliative care increased from 8.5% to 57.2% (23).…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Communication around treatment decisions are often delayed and tend to take place in the inpatient setting, where mortality is high, especially in conditions such as decompensated cirrhosis. [8][9][10][11] One reason for such delayed and limited communication in this high-risk population may be gaps in training for general and subspecialty gastroenterology (GI) fellows. Prior studies have demonstrated low quality of communication among GI fellows when discussing end-of-life care.…”
Section: Introductionmentioning
confidence: 99%